Laptop computer induced erythema ab igne: A new presentation of an old disease - Salvio, Ana Gabriela [UNESP]; Nunes, Adauto Jose; Angarita, Dora Patricia Ramirez (FapUNIFESP (SciELO), 2016)
Erythema ab igne is a condition characterized by skin changes due to chronic exposure to moderate temperature. We describe a female patient with continuous use of a laptop computer on exposed legs for 6 months and consequent development of reticulated hyperpigmentation at the area. Histopathological examination revealed epidermal atrophy, collagen fragmentation, and vacuolar changes in the basal layer, among other signs. We consider this case to be a modern cause of erythema ab igne.
Keywords: Hot temperature; Hyperpigmentation; Infrared rays